Business Value Added Analysis Copr Processing In UD. Copr Down In Wantulasi Village, Sub-District Of Wakorumba Utara, Buton Utara Regency - Bayu Harisakti; Hermanto Hermanto; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to determine the copra production process in Wantulasi Village, North Wakorumba District, North Buton Regency, and calculate the added value of copra in Wantulasi Village, North Wakorumba District, North Buton Regency. Determination of the research location purposively. Data was collected using observation, interviews, recording, and questionnaires. The analysis used is value-added analysis. Based on the results of research conducted on the value-added analysis of copra processing in Wantulasi Village, North Wakorumba District, North Buton Regency, it can be that the income received at UD. Copra Turuni is Rp.26,250,000. while for added value after processing, the added value is Rp. 3,947/kg per three months in one production and 1 kg of copra is comparable to 3 coconuts with a value ratio of 77%. The income earned by copra farmers from processing coconuts into copra increased, with the copra price being Rp.7500.